The Effect Of A Mobile Device User Interface Design Based On Personality Nuances On Learner's Perceptual Experience And Satisfaction - Sarsam, Samer Muthana (2018)
User experience (UX) encompasses the concepts of usability and affective engineering. It is a crucial factor in the design of mobile devices. However, it has been difficult to gain a common understanding of the design characteristics that suit the different personalities of individuals when using mobile device technology. Therefore, in this thesis, a novel design of a mobile UI-based on the personality nuances was proposed. It was argued that such design would stimulate information processing in according to learners‘ mental model in order to obtain an effective and satisfying learning experience with a mobile phone. A total of 87 undergraduate students (15 male, and 35 female) were participated in this study.